Bionomic aspects of the Anopheles subpictus species complex in Sri Lanka - Pavillupillai, J.J.; Ramasamy, R.; Surendran, S.N. (My University, 2014)
Anopheles subpictus Grassi s.l. (Diptera: Culicidae) functions as a secondary malaria vector to Anopheles culicifacies Giles s.l. (Diptera: Culicidae) in Sri Lanka. The taxon A. subpictus is reported to exist as a species complex comprising four sibling species (A–D) that can be differentiated through polytene chromosome banding patterns and stage-specific morphometric traits in India. Based on the morphological characteristics described for the Indian Subpictus Complex, the presence of all four sibling species has been described in Sri Lanka. As sibling species show distinct bio-ecological characteristics that are important for devising appropriate vector control measures, a study was carried out in six districts in the dry zone of Sri Lanka. The results confirm the presence of all four sibling species, with species C predominating in inland areas and species B in coastal areas. Species C and D were indoor-resting and indoor-feeding, while species B was outdoor-resting with no significant preference for indoor- or outdoor-resting. Species B showed distinct morphological variation in the ornamentation of wings and palpi. Blood meal analysis revealed that species B, C, and D can feed on humans as well as cattle. The differential bio-ecological traits shown by the members of the Subpictus Complex are important for developing appropriate vector control measures in Sri Lanka.
Keywords: feeding preference; malaria; mosquito vectors; sibling species